EFFECTS OF DIFFERENT TEMPERATURE ON CONCRETE BY ADDING GLASS FIBER, STEEL FIBER AND POLYPROPYLENE FIBER WITH RIVER SAND - Venkadachalam, Gokulnath; M., Dileep kumar (International Journal of Psychosocial Rehabilitation, 2020)
The paper introduces an examination concerning the productivity of temperature-delicate self-compacting concrete. Inspecting on self-compected solid, steel fiber, glassfiber, and polypropylene fiber to this end, adding strands (steel fiber,glassfiber, and polypropylene), using rivers, and content 1.2% for blend of solidmaterial When the tests were 7, 14, and 28 days old. They have been warmed to high temperatures. Every example were warmed to various temperatures for each solid blend (0°C, 100°C, 200°C). Then Tests for weight reduction and compressive quality were performed. The Observations of surface breaks were made after presentation to high temperatures A critical loss of solidarity for all cements after 200°C was watched, Especially for concrete containing Polypropylene fiber,glassfiber, and steel fiber. The strands decreased the danger of dangerous spalling and forestalled it Based on the consequences of the investigation, the yield of fine total cement can be induced